Community Empowerment of Jatiduwur Village through Puppet Mask Performance Art Training to Improve the Creative Economy of Jatiduwur Community - Wahyudi, Wahyudi; Sari, Ayu Titis Rukmana; Mukmin, Bagus Amirul; Sahari, Sutrisno; Hunaifi, Abdul Aziz; Zaman, Wahid Ibnu; Aka, Kukuh Andri; Wati, Epritha Kurnia; Dwiyanti, Linda (CV. Srikandi Kreatif Nusantara in collaboration with Institut Teknologi Mojosari Nganjuk, 2024)
Jatiduwur, a village in the northern part of Jombang district, is renowned for its Wayang Topeng art. By nurturing this art form, Jatiduwur can uplift its community spirit and promote Jombang as a guardian of cultural heritage. The focus extends beyond modernizing performances and training new talent; it also includes creating marketable mask products to boost economic growth. Youth organizations and PKK members undergo training to sustain the tradition and establish a business network. Program activities encompass coordination, socialization, and four training sessions covering storyline composition, dance music innovation, souvenir crafting, and marketing strategies. Outcomes include the establishment of a Jatiduwur art studio with 37 performers, official registration, and the formation of a business group involving 17 PKK members. This initiative has not only enriched the cultural landscape but also enhanced community income through performances and merchandise sales, including t-shirts, keychains, and masks, with notable sales figures.